Associations Between Erythrocyte Membrane Fatty Acid Compositions and Biomarkers of Vascular Health in Adults With Type 1 Diabetes With and Without Insulin Resistance: A Cross-Sectional Analysis - Rachel Churm (Canadian Journal of Diabetes, 2021)
PurposeThe aim of this study was to assess the relationship between specific erythrocyte fatty acids levels and vascular health in type 1 diabetes (T1D) with and without insulin resistance (IR).MethodsWe analysed baseline pretreatment data in a subset of 23 patients with T1D from a previously published randomised controlled trial consisting of comprehensive erythrocyte-derived fatty acid profiles and a panel of inflammation-associated endothelial markers. Estimated glucose disposal rate was used to identify and categorise patients with IR. We utilised principal component analysis (PCA) to cluster vascular biomarkers to compute a single ‘vascular signal’ and employed univariate linear regression models to investigate the association with IR and fatty acid profiles.ResultsSubjects with IR displayed significantly higher levels of linoleic acid (p=0.001), lower levels of eicosapentaenoic acid (EPA) (p<0.001), lower total omega-3 polyunsaturated fatty acid (n-3PUFA) (p<0.006), and an increased n-6PUFA:n-3PUFA ratio (p=0.001). IR was associated with significantly higher linoleic acid levels, total n-6PUFA, and an increased ratio of n-6PUFA:n-3PUFA, and negatively associated with arachidonic and eicosapentaenoic acid levels, total saturated fatty acid, and total n-3PUFA. The PCA-derived vascular biomarker cluster was positively associated with linoleic acid, n-6PUFA:n-3PUFA ratio and inversely associated with EPA.ConclusionSpecific erythrocyte membrane fatty acid compositions are associated with impaired vascular health and IR in adults with T1D. These findings suggest that IR and risk of associated complications may be influenced by specific fatty acid profiles, and thus potentially modified by the selective targeting of dietary fatty acids.